Effect of contact resistance in organic field‐effect transistors. Issue 9 (24th March 2021) - Shi, Yanjun; Liu, Jie; Hu, Yuanyuan; Hu, Wenping; Jiang, Lang
Abstract: Contact resistance ( R C ) is universally present in organic field‐effect transistors (OFETs) and the performance of OFETs can be easily affected by R C, which will result in poor performances such as low mobility ( μ ), large threshold voltage ( V T ), and non‐ideal transfer/output characteristics. In this article, we provide a comprehensive review on the effects of R C in OFETs. We start with a brief introduction of the origin of R C and its effects on OFETs, followed by the commonly used methods for extraction of R C . Then, methods for reducing R C are thoroughly discussed. Especially, fabricating monolayer molecular crystal (MMC) OFETs is highlighted as one of the key solutions to reduce R C effectively. The final section describes the challenges in MMCs preparation and concludes with an outlook for further reducing R C to enhance the performances of OFETs. Abstract : This review provides a comprehensive review on the effects of contact resistance in organic field‐effect transistors and strategies how to reduce it. Especially, fabricating organic field‐effect transistors based on monolayer molecular crystal is highlighted as one of the key solutions to reduce contact resistance effectively.